Ancestry deconvolution and partial polygenic score can improve susceptibility predictions in recently admixed individuals - Davide Marnetto (Nature Portfolio, 2020)
Polygenic scores are believed to hold future promise for trait prediction and personalized medicine, but are sensitive to demographic history. Here, Marnetto et al. develop partial polygenic scores supplemented with local ancestry deconvolution which improves prediction accuracy into recently admixed European populations.